Assessment of the Impact of Macroeconomic Factors on Wage Formation in a Market Transformation of Ukraine’s Economy - Yakymchuk, Alina; Polishchuk, Olena; Mykytyn, Taras (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional Development, 2021)
An assessment of the impact of macroeconomic factors on wage formation in conditions of market transformation of Ukraine’s economy has been performed. The factor analysis of indicators has been carried out. The main factors of earning power in the Republic of Poland and Ukraine are compared. The main problems of state regulation of wage setting in Ukraine are revealed. The measures to improve macroeconomic regulation of the wage process and increase macroeconomic indicators have been proposed.